2021
DOI: 10.3390/catal11060671
|View full text |Cite
|
Sign up to set email alerts
|

Design of Iridium N-Heterocyclic Carbene Amino Acid Catalysts for Asymmetric Transfer Hydrogenation of Aryl Ketones

Abstract: A series of chiral complexes of the form Ir(NHC)2(aa)(H)(X) (NHC = N-heterocyclic carbene, aa = chelated amino acid, X = halide) was synthesized by oxidative addition of -amino acids to iridium(I) bis-NHC compounds and screened for asymmetric transfer hydrogenation of ketones. Following optimization of the reaction conditions, NHC, and amino acid ligands, high enantioselectivity was achieved when employing the Ir(IMe)2(l-Pro)(H)(I) catalyst (IMe = 1,3-dimethylimidazol-2-ylidene), which asymmetrically reduces a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…[22] Structural and computational studies on the binding properties of amino acid coordination complexes have been reported in literature. [23,24] We decided to undertake a computational study using Density Function Theory (DFT), including dispersion empirical corrections, to clarify the reasons for the relative stabilities and interconversions of the complexes of the hyperpolarization catalyst with a series of amino acids (Gly, Ala, Val) of increasing side chain bulk. As in the case of our earlier DFT study, [13] the relative energies of the complexes can be used to calculate populations that can be validated with the experimental NMR abundances.…”
Section: Introductionmentioning
confidence: 99%
“…[22] Structural and computational studies on the binding properties of amino acid coordination complexes have been reported in literature. [23,24] We decided to undertake a computational study using Density Function Theory (DFT), including dispersion empirical corrections, to clarify the reasons for the relative stabilities and interconversions of the complexes of the hyperpolarization catalyst with a series of amino acids (Gly, Ala, Val) of increasing side chain bulk. As in the case of our earlier DFT study, [13] the relative energies of the complexes can be used to calculate populations that can be validated with the experimental NMR abundances.…”
Section: Introductionmentioning
confidence: 99%
“…The new ligands represent N-Boc-Data taken from ref. [98,99]. It was shown that the nature of R in Cp* R dramatically affects both selectivity and the rate of the reaction.…”
Section: Asymmetric Transfer Hydrogenation (Ath)mentioning
confidence: 99%
“…Later, the same research team [99] synthesized new complexes Ir(NHC) 2 (L)(H)(X) (20), which were active in ATH of ketones. The maximum enantioselectivity was achieved in the presence of the Ir(IMe) 2 (L-Pro)(H)(I) Ir(IMe) 2 (L-Pro)(H)(I) catalyst, which reduced some acetophenone derivatives with ee up to 95%.…”
Section: Asymmetric Transfer Hydrogenation (Ath)mentioning
confidence: 99%
“…For example, the Special Issue summarizes efforts in the area of homogeneous catalysts concerning iridium catalysts containing NHC ligands applied to the asymmetric transfer hydrogenation of ketones [4], synthesis of quinoxalines from glycerol and diamines [5], cross coupling for natural product synthesis [6], and palladium-catalyzed reductive carbonylation of nitro-styrene [7]. This Special Issue also introduces efforts entitled "Immobilization of Rh(I)-N-Xantphos and Fe(II)-C-scorpionate onto magnetic nanoparticles [8]" and "5-(2-Pyridyl)tetrazolate complex of molybdenum(VI)" as precursors for reusable molybdenum oxide-based hybrid heterogeneous catalyst [9].…”
mentioning
confidence: 99%